ANALISIS KARAKTERISTIK MEMBRAN PENGOLAHAN AIR DARI BAHAN POLYETHERSULFONE DENGAN PENAMBAHAN PERAK NITRAT - Agung Mataram; Nasution, J.D; Bizzy, I; Mohruni, A.S; Rizal, S; Pataras, M; Kurnia, A.Y; Kurnia, R.D; Jambak, M.I; Bactiar, M; Sutanto, H (Politeknik Negeri Sriwijaya, Indonesia, 2024)
In this research, the membrane was made from polymers made from Polyethersulfone (PES), Silver Nitrate (AgNO3) strengthening agent, and additional solvent N,N-Dimethylformamide (DMF). The comparison in each sample is 1.5wt%, 2wt%, and 2.5wt%. The solution is connected to DC electricity with a voltage of 15000V for 30 seconds. The tensile test shows that as the mixture concentration increases, the membrane tensile strength or the membrane's ability to withstand loads tends to decrease, where the PES@AgNO3 membrane with a concentration of 1.5wt% has the highest average tensile strength value, namely 5.74206 MPa, then the value The lowest average tensile strength was found in the PES@AgNO3 membrane with a concentration of 2.5wt%, namely 3.07480 MPa. The decrease in the tensile strength value was caused by the uneven distribution of pores and agglomeration formed so that when the tensile test was carried out the membrane became more brittle and breaks easily. In the CWP test, there was a significant decrease in flux results with variations in membrane concentration, where when the PES@AgNO3 membrane mixture concentration was 1.5wt%, the highest flux value reached 3.88797 L.m-2.h-1.bar-1, inversely proportional to the increasing the concentration of the membrane mixture, namely 2.5wt%, obtained the lowest flux value, namely 1.01345 L.m-2.h-1.bar-1.